Politically connected CEOs and earnings management: evidence from China. Issue 3 (2nd July 2016) - Chi, Jing; Liao, Jing; Chen, Xiaojun
ABSTRACT: This paper examines the impact of politically connected CEOs on earnings management in Chinese listed firms. The results show that firms with politically connected CEOs engage in significantly lower levels of accrual-based earnings management than firms without politically connected CEOs. We then find evidence that firms with politically connected CEOs conduct significantly higher levels of real earnings management, which is more difficult to detect than accrual-based earnings management, and that in non-state-controlled firms, where government support is less, the presence of politically connected CEOs is positively related to accruals manipulation. We draw regulators' attention to the fact that using accrual-based earnings management measures alone may underestimate the earnings management activities of firms with politically connected CEOs. Our findings are robust after controlling for possible endogeneity.